Space-Time Generalization of R-Function Method (ST-RFM) - Wawrzynek, Andrzej (Computer Assisted Methods in Engineering and Science, 2023)
A generalized, space-time version of the R-function method has been presented. The general structure of the solution for the space-time problem and the algorithm for the determination of the unknown parameters of the structure have been given. The considerations are illustrated by two numerical examples: the first one concerns the cooling of a square plate, while in the second one more complex shape of domain is considered. The numerical solution of the first problem is compared with the solution obtained on the basis of FDM.